MANAJEMEN SARANA DAN PRASARANA DALAM PENGEMBANGAN KARAKTER SISWA DI SDIT ASSALAAM SANDEN - Mila Mutiara Choirunisa; Dewi Rizqa Tamia; Yusuf Atma Suryabudi; Zainal Arifin Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines the role of facilities and infrastructure management in character development among students at SDIT Assalaam Sanden, Bantul. Using qualitative methods through interviews and observations, the study analyzes how educational facilities such as the mosque, classrooms, library, and sports facilities are utilized to shape students' Islamic character. The mosque serves not only as a place of worship but also as a means of habituating communal prayers and Quran memorization (tahfidz). Meanwhile, classrooms and the library support the teaching of religious values. Sports facilities play a role in fostering sportsmanship and teamwork among students. The results show that well-managed facilities and infrastructure support the formation of student character, including discipline, responsibility, and ethics. Effective management ensures that these facilities consistently support sustainable and holistic learning. The research concludes that facility management integrated with Islamic values significantly contributes to shaping students' noble character, not only academically but also morally and spiritually, providing them with valuable preparation for the future.